Reading aesthetics and philosophy of art : selected texts with interactive commentary / [compiled by] Christopher Janaway. - Janaway, Christopher (Blackwell, 2005)
Designed for readers with no or little prior knowledge of the subject, this concise anthology brings together key texts in aesthetics and the philosophy of art.